Analisis Hasil Belajar Seni Kriya pada Mata Pelajaran SBDP Siswa Kelas III di SD Negeri 1 Lubuk Ketepeng - Winda, Winda; Yulaini, Erma; Laksana, Robert Budi (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Learning outcomes are said to be achieved if students experience development and improvement in behavior in which the formulation of learning objectives is proven and demonstrated by the teacher to students through the tests or exams they take. Through the results of interviews before the research, the class III teacher explained that he still experienced obstacles in choosing the right media and methods. In this study, researchers conducted research at SD Negeri 1 Lubuk Ketepeng. In this research, researchers used qualitative descriptive methods. Therefore, further research is needed when researchers go directly to the location being studied. In theory, qualitative research is about testing a hypothesis or theory, whereas in qualitative research it is about finding a theory. This research uses three methods in the data collection process, namely observation, interviews and documentation. The results of the analysis of observations that the researcher carried out at SD Negeri 1 Lubuk Ketepeng on students III, overall the researcher concluded that the results of learning craft arts in the SBDP subject material cutting, sticking, connecting for class III students were still in the Fair category with average value 66.36℅. Through the results of observation analysis, interviews and data documentation carried out by researchers. This research can be concluded that the learning outcomes of SBDP learning on cutting, sticking and folding material in class III of SD Negeri 1 Lubuk Ketepeng are in the sufficient category with a percentage of 0.52℅. With different criteria patterns according to their respective advantages. There are two factors that influence student learning outcomes, namely internal and external factors.